2017
DOI: 10.1002/jmri.25898
|View full text |Cite
|
Sign up to set email alerts
|

Multiparametric characterization of response to anti‐angiogenic therapy using USPIO contrast‐enhanced MRI in combination with dynamic contrast‐enhanced MRI

Abstract: 1 Technical Efficacy: Stage 2 J. Magn. Reson. Imaging 2018;47:1589-1600.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…Posttreatment scans using the same protocol were performed 2 days later. In a previous study, we showed that this regimen significantly reduced the blood volume, vascular density, and K trans of TOV-21G tumors (26).…”
Section: Methodsmentioning
confidence: 80%
“…Posttreatment scans using the same protocol were performed 2 days later. In a previous study, we showed that this regimen significantly reduced the blood volume, vascular density, and K trans of TOV-21G tumors (26).…”
Section: Methodsmentioning
confidence: 80%
“…This would limit the quantitative reliability of T1 weighted imaging for IONPs in vivo. Considering the potential benefits of longitudinal studies, there have been efforts to utilize quantitative T1 mapping of the effects of IONPs in rodent studies 41,42 . The T1 (or R1) mapping provided objective quantification of IONPs induced R1 (= 1/T1) enhancement.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasmall superparamagnetic iron oxides (USPIOs) are high-contrast MRI contrast agents which are very small and are useful in assessment of the blood pool. Currently, they are more frequently utilized in research settings but are helpful in evaluating vessel characteristics, such as size or density [27] (Figure 5). discontinued gadofosveset trisodium, extravasates at sites of angiogenesis, but also can leak from normal blood vessels.…”
Section: Invasive and Non-invasive Imaging Methodsmentioning
confidence: 99%